Study on children psoriasis in Latvia - Sigure, Sanita (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2002)
Objective. The aim of the study was to evaluate psoriasis morbidity among children in Latvia. Materials and methods. 252 psoriatic children, 3 to 18 years old children, were surveyed using a questionnaire developed for this study. Data on the course of the disease, skin involvement and further clinical symptoms and signs were registered. They were evaluated using PASI system. Data were analyzed using the computerized programs (MS Excel 98 and SPSS). 149 girls (59 %) and 103 boys (41 %) were included in the study, the patients originated from different regions of Latvia. Results. Children aged 11 to 15 years suffered from psoriasis (46%) most frequently. Psycho-emotionalstress 198 (79%), viral and bacterial infections 119 (47%) were the most frequent promoting factors. In 26% of patients a family history of psoriasis was noted. Psoriasis vulgaris was diagnosed in 57 % of patients, and psoriasis exsudativa in 27 %. Mean PASI index was 12.92. Conclusion. Psoriasis seems to be quite frequent in children in Latvia.
Keywords: Adolescenca; Adolescence; Age factors; Ankete; Child; Comorbidity; Epidemiology; Latvia; Latvija; Otrok; Psoriasis; Psoriaza; Questionnaires; Sex factors; Soobolevnost; Spolni dejavniki; Starostni faktorji